2010
DOI: 10.1007/s12649-010-9029-3
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Precious Metals by Selective Adsorption on Dimethylamine-Modified Persimmon Peel

Abstract: Dimethylamine (DMA) functional group was grafted to obtain modified persimmon peel gel (DMA-PP) with the focus of development of selective recovery of gold as well as other precious metals like palladium and platinum. The adsorption behavior of the DMA-PP gel for various metal ions at varying hydrochloric acid concentrations has been studied. It was found that the DMA-PP exhibits high affinity for Au(III) as well as for Pt(IV) and Pd(II) and no affinity for base metals such as Cu(II), Fe(III), Ni(II), and Zn(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Although, as mentioned earlier, CPT and PP gels were found to exhibit extraordinary high selectivity for gold(III), we further attempted to enhance the affinity also for platinum(IV) and palladium [35][36][37][38][39][40]. It is easy to chemically modify persimmon tannin extract and persimmon waste including persimmon peel by immobilizing a variety of functional groups which exhibit special affinities for some metal ions onto their surface similar to other biomass wastes [41,42].…”
Section: Chemical Modification Of Persimmon Tannin Extract and Persimmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, as mentioned earlier, CPT and PP gels were found to exhibit extraordinary high selectivity for gold(III), we further attempted to enhance the affinity also for platinum(IV) and palladium [35][36][37][38][39][40]. It is easy to chemically modify persimmon tannin extract and persimmon waste including persimmon peel by immobilizing a variety of functional groups which exhibit special affinities for some metal ions onto their surface similar to other biomass wastes [41,42].…”
Section: Chemical Modification Of Persimmon Tannin Extract and Persimmentioning
confidence: 99%
“…It is easy to chemically modify persimmon tannin extract and persimmon waste including persimmon peel by immobilizing a variety of functional groups which exhibit special affinities for some metal ions onto their surface similar to other biomass wastes [41,42]. In our research works, persimmon waste was chemically modified by immobilizing functional group of dimethylamine (DMA) to prepare the adsorption gel functioning as a typical weak base type of anion exchange material and investigated its adsorption behavior for some precious and base metals from hydrochloric acid solutions [35,36]. Further, a variety of adsorption gels were prepared from persimmon tannin extract powder by the chemical modifications immobilizing other functional groups such as tertiary amine where the immobilized tertiary amine groups function as quaternary ammonium compounds (QA) [37], a typical strong base, as well as tetraethylenepentamine (TEPA) [38], glycidyltrimethyl ammonium (GTA), aminoguanidine (AG) [40], and bisthiourea (BTU) [41].…”
Section: Chemical Modification Of Persimmon Tannin Extract and Persimmentioning
confidence: 99%
“…Some ligands such as 2-aminothiazole, N-aminoguanidine, Plant tannin, Bisthiourea, Dimethylamine, and Ethylenediamine have been used to modify phenolic compounds and tannins to adsorb metal ions from e-waste. These ligands increase the adsorption capacity and allow the precious metals to be selectively recovered from base metals by forming complexes with them [ 6 , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%
“…3–7 However, when these structures are used as they are, they may cause poor adsorption performances in cases where appropriate functional groups are not considered. 8…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, when these structures are used as they are, they may cause poor adsorption performances in cases where appropriate functional groups are not considered. 8 It has been shown in various studies that phenolic hydroxide groups have high adsorption and reduction capacities, especially in the recovery of precious metals and platinum group metals such as Au, Ag, Pd, Pt, etc. [9][10][11] We have reported that the pyrogallol molecule, a phenol containing three hydroxyl functional groups attached to the benzene ring, can reduce precious metal ions to the metallic state.…”
Section: Introductionmentioning
confidence: 99%